Influence of Throttling and Nozzles Switching Sequence on Indicator of Water Distribution Uniformity in Cooling Tower Model - Vadym Orel; Oksana Matsiyevska; Bohdan Pitsyshyn; Maksym Tseniukh (Energy Engineering and Control Systems, 2023)
The article analyzes factors leading to non-uniformity of water distribution in cooling towers. These include imperfections in the design of pipelines and nozzles of the water distribution system of cooling towers. Previous studies conducted on a model of the water distribution system of the tower-type cooling system at Rivne Nuclear Power Plant have revealed uneven water distribution on the nozzles. Simulation of the simultaneity of nozzle activation showed that the nozzle that is activated first has the highest flow rate. Therefore, to achieve acceptable uniformity of water distribution, this nozzle was throttled using a throttling orifice plate. It has been shown that such throttling is effective even in the presence of hydrodynamic cavitation at orifice plate diameter ratios of 0.449...0.624. When four model nozzles are activated one after the other, the flow rate of the first nozzle decreases both with and without throttling. At the same time, increase in the number of working nozzles up to four does not significantly affect the flow rate of the first nozzle.